2018
DOI: 10.1038/s41467-018-04122-x
|View full text |Cite
|
Sign up to set email alerts
|

Direct binding of CEP85 to STIL ensures robust PLK4 activation and efficient centriole assembly

Abstract: Centrosomes are required for faithful chromosome segregation during mitosis. They are composed of a centriole pair that recruits and organizes the microtubule-nucleating pericentriolar material. Centriole duplication is tightly controlled in vivo and aberrations in this process are associated with several human diseases, including cancer and microcephaly. Although factors essential for centriole assembly, such as STIL and PLK4, have been identified, the underlying molecular mechanisms that drive this process a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 60 publications
(65 reference statements)
0
35
0
Order By: Relevance
“…Although our model is formulated for mammalian cells, the principles of PLK4 symmetry breaking outlined above are likely to be conserved also in other organisms. Further concerted experimental and theoretical efforts will be required to increase the biological realism and predictive power of the model by the refinement of molecular mechanisms and incorporation of additional molecular players, such as CEP85, which was recently implicated in PLK4 activation ( Liu et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although our model is formulated for mammalian cells, the principles of PLK4 symmetry breaking outlined above are likely to be conserved also in other organisms. Further concerted experimental and theoretical efforts will be required to increase the biological realism and predictive power of the model by the refinement of molecular mechanisms and incorporation of additional molecular players, such as CEP85, which was recently implicated in PLK4 activation ( Liu et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Third, both satellites and a subgroup of P‐body proteins have been shown to move along MTs (Dammermann & Merdes, ; Aizer et al , ). Finally, a recent BioID‐based study on RNA bodies identified the centrosomal protein CEP85, a regulator of centriole duplication and PLK4 activity (Liu et al , ), as a high‐confidence prey for multiple P‐body baits. These observations suggest that satellites and centrosomes may play a yet undescribed role related to RNA processing and decay.…”
Section: Discussionmentioning
confidence: 99%
“…While our model is formulated for mammalian cells, the principles of PLK4 symmetry breaking outlined above are likely to be conserved also in other organisms. Further concerted experimental and theoretical efforts will be required to increase the biological realism and predictive power of the model by the refinement of molecular mechanisms and incorporation of additional molecular players, such as CEP85, which was recently implicated in PLK4 activation (Liu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%